Tinjauan Pustaka Dampak Keandalan E-Servqual Terhadap Kepuasan Pelanggan Dalam E-Commerce - Wulan, Indra; Safuan, Safuan; Erwin, Erwin (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2024)
The 84% dissatisfaction rate of e-commerce customers in Indonesia is an important indicator for e-commerce managers to improve service performance and build lasting relationships with online consumers. Various methods can be used by companies to evaluate service quality, and one of the popular ones is E-SERVQUAL. This research uses a qualitative method with a systematic literature review, it is hoped that business practitioners can gain insight into the factors that affect Servqual reliability and customer satisfaction in e-commerce. This research uses the Google Scholar platform to obtain literature, resulting in 7 relevant scientific articles. Converging literature findings over the past five years confirm that improvements in e-service quality consistently result in increased levels of consumer satisfaction with different e-commerce platforms. Online business has played an important role in digital marketing, yet many companies have yet to maximise its potential. With the continuous development in the competitive e-commerce industry, service quality is the key to winning over customers. Companies must be responsive to digital trends and utilise new technologies to improve efficiency and effectiveness. Although this study has provided an overview of e-servqual and customer satisfaction in Indonesian e-commerce, future quantitative research would be beneficial to complement the findings and provide deeper insights with quantitative research with methods such as surveys or experiments recommended to examine cause-and-effect relationships and measure variables numerically. Future research could explore less common e-commerce business models, such as crowdfunding platforms, social e-commerce, or specialised online marketplaces.